2001
DOI: 10.1212/wnl.57.3.467
|View full text |Cite
|
Sign up to set email alerts
|

Randomized placebo-controlled trial of donepezil in patients with progressive supranuclear palsy

Abstract: The findings suggest that acetylcholinesterase inhibitors such as donepezil have at best selective, modest effects on cognition in patients with PSP. In light of its deleterious effects on ADL/mobility, donepezil is not recommended for this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(73 citation statements)
references
References 45 publications
3
67
0
3
Order By: Relevance
“…6,7 In PSP, anterior frontal lobe dysfunction is the most disabling cognitive deficit, partly due to marked deafferentation of the prefrontal areas, resulting from degeneration of striatothalamocortical pathways. 8,9 The circuits implicated in behavioral control involve the thalamus, mainly the medial thalamus connected to the fronto-orbital cortex and the anterior thalamus connected to the cingulate gyrus. 10 In CBD, cognitive and motor dysfunctions are frequent, and the most characteristic higher cortical disorders are limbkinetic apraxia, ideomotor apraxia, and alien limb phenomenon, probably related to damage to the perirolandic regions.…”
mentioning
confidence: 99%
“…6,7 In PSP, anterior frontal lobe dysfunction is the most disabling cognitive deficit, partly due to marked deafferentation of the prefrontal areas, resulting from degeneration of striatothalamocortical pathways. 8,9 The circuits implicated in behavioral control involve the thalamus, mainly the medial thalamus connected to the fronto-orbital cortex and the anterior thalamus connected to the cingulate gyrus. 10 In CBD, cognitive and motor dysfunctions are frequent, and the most characteristic higher cortical disorders are limbkinetic apraxia, ideomotor apraxia, and alien limb phenomenon, probably related to damage to the perirolandic regions.…”
mentioning
confidence: 99%
“…Early clinical trials in PSP employed drug treatment to correct alterations in the dopaminergic, cholinergic, and gamma-amino butyric acid (GABA)ergic pathways and produced limited evidence of benefit. Trials with both physostigmine and donepezil were employed with a poor response in memory as well as motor function [31,32]. As about GABAergic agonists, trials with zolpidem [33] and gabapentin [34] found, respectively, transient improvement in eye movements and inhibitory frontal function.…”
Section: Current Pharmacological Chances In Apsmentioning
confidence: 99%
“…One [141] double-blind placebo-controlled randomized crossover trial (level I of evidence) randomized 22 patients (mean age: 66 years). One patient dropped out before the treatment had started.…”
Section: The Efficacy Of Donepezil In Pspmentioning
confidence: 99%
“…Thus, in this study it was impossible to differentiate whether worsening in motor ADL function was primarily caused by insufficient drug medication or due to progression of parkinsonian syndromes. Litvan et al [141] reported 3 patients who did not tolerate the full dose of donepezil because of considerable deterioration of motor functions. The frequency of diarrhoea was higher in the donepezil phase compared with the placebo period.…”
Section: The Efficacy Of Donepezil In Pspmentioning
confidence: 99%